2009
DOI: 10.1002/art.25008
|View full text |Cite
|
Sign up to set email alerts
|

Do mothers and fathers hold similar views about their child's arthritis?

Abstract: Objective. Evaluations of the well-being of children with juvenile idiopathic arthritis (JIA) typically rely on parents as proxy respondents. An assumption of several studies appears to be that mothers' and fathers' ratings are interchangeable, as reports do not always specify which parent completed the assessments nor, in repeated measures, whether they were completed by the same parent. The aim of this study was to examine the level of agreement between mothers' and fathers' ratings of their child's quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
1
19
3
1
Order By: Relevance
“…The present ICC values were also greater than those reported in children and adolescents with cancer (0.22-0.68) [24] and sickle cell disease (0.30-0.45) [65]. The present greater ICC values may have resulted from the large percentage of female patients and their mothers being surveyed; however, this dyad gender effect has not been observed previously [16,54,66]. While still significant, the lower observed ICC of 0.48 for the PedsQL TM parent-child Physical Health Summary Scores for 8-12 year olds may represent greater self-perception and self-awareness of physical limitations in the younger child.…”
Section: Discussioncontrasting
confidence: 80%
“…The present ICC values were also greater than those reported in children and adolescents with cancer (0.22-0.68) [24] and sickle cell disease (0.30-0.45) [65]. The present greater ICC values may have resulted from the large percentage of female patients and their mothers being surveyed; however, this dyad gender effect has not been observed previously [16,54,66]. While still significant, the lower observed ICC of 0.48 for the PedsQL TM parent-child Physical Health Summary Scores for 8-12 year olds may represent greater self-perception and self-awareness of physical limitations in the younger child.…”
Section: Discussioncontrasting
confidence: 80%
“…Agreement between mothers and fathers has been reported as good, 3 although agreement in ratings of current levels of pain were less concordant between children and their fathers compared with children and their mothers. Mulligan et al 30 also found disagreement between mothers and fathers in their assessment of their child’s JIA, although the direction of the disagreement was not systematic. Neither of these studies provided specific analysis on adolescents limiting comparison with this study.…”
Section: Discussionmentioning
confidence: 98%
“…Participants were recruited as part of the SPARKS Childhood Arthritis Response to Medication Study (SPARKS-CHARMS), which examines genetic, immunobiological and psychological aspects of response to MTX or anti-TNF therapy given for arthritis [9,10,12,13]. The study recruits children of any age with juvenile idiopathic arthritis (JIA), defined by ILAR criteria [14], who are under the care of the Rheumatology service at Great Ormond Street Hospital for Children (GOSH) or the Adolescent Rheumatology service at University College Hospital, London, UK.…”
Section: Methodsmentioning
confidence: 99%
“…Although fathers and the patients themselves participated in the study, mothers were the largest respondent group. We have previously shown that there can be high levels of discordance between mothers’ and fathers’ views about their child’s JIA [9], and others have reported discordance between parent and child reports [16], so to help ensure consistency we have limited this analysis to reports from one parent (mothers). This analysis is restricted to mothers of those children in the study who had taken MTX for at least six months, and were still taking it at the time the questionnaires were completed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation